Malaysian fisheries policy: search for new grounds - Hj Omar, Ishak; Mohd Noh, Kusairi; Raja Abdullah, Nik Mustapha; Kuperan, K. (Elsevier, 1992)
Past fisheries development policies in Malaysia are assessed and new grounds for managing the Malaysian fisheries are explored. Some incompatibility in the goals for fishery development are discerned, especially those of increasing domestic landings through mechanization and resource conservation. Future management efforts should be based on a fuller understanding of the fishery stock and regional management of fish stocks. Aquaculture is often seen as a plausible alternative in order to augment supplies from the capture fisheries. A comprehensive multidisciplinary approach is needed to transform and commercialize traditional, experience-dependent culture systems into technology-packaged systems based on scientific methods. There is also substantial potential for the development of recreational fisheries.